Tingkat Pengetahuan Ibu tentang Sinusitis di Dusun VII Desa Sei Mencirim Kecamatan Kutalimbaru Kabupaten Deli Serdang - Katini Katini; Ade Irma Triana Siregar (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2022)
Sinusitis is a disease that occurs in the sinus area. The sinuses are air cavities that are in the area of the face connected to the nose. The function of the sinus cavity itself is to keep the nose moist and maintain air exchange in the nasal area. The research design used in this study is descriptive quantitative in nature aiming to determine the mother's level of knowledge about sinusitis. Sampling was carried out using